Desain Instruksional Modul Perkuliahan Literasi Baca Tulis Responsif Gender untuk Mendorong Kesetaraan dan Inklusi di Pendidikan Dasar - Kemil Wachidah; Ahmad Fathoni (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to develop gender-responsive literacy modules to improve the competencies of students in the Primary School Teacher Education Program (PGSD) at Muhammadiyah University Sidoarjo. The problem identified is the low literacy skills of students, which are influenced by the lack of learning modules that integrate principles of gender equity and sensitivity. Additionally, gender-based literacy achievement gaps due to social stereotypes pose a significant challenge in the learning process. The research method employed is Design-Based Research (DBR) with an iterative and collaborative approach between researchers and education practitioners. Data collection was conducted through pretest-posttest assessments, attitude and perception questionnaires, observations, and interviews to evaluate the effectiveness and validity of the modules during the implementation process. Quantitative data analysis used descriptive statistics, while qualitative data was analyzed thematically. The results of the study indicate that the gender-responsive literacy module developed is able to meet academic standards and the learning needs of students in an inclusive manner. The level of acceptance of the module in terms of usage, content, and response achieved scores between 86% and 97%, which is considered very good. The module also successfully instilled critical awareness of gender issues in literacy learning and supported the development of adaptive and equitable literacy skills for all PGSD students. This study recommends expanding the scope of the module and providing ongoing training for teachers so that gender-responsive principles can be optimally applied in basic education.